Econometric analysis of the wealth gap between East and West Germany - Gideon Becker (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
Nearly 25 years after the German reunification, vastly different living conditions between East and West Germany still remain. This is particularly true for the distribution of net wealth which is of special importance for the well-being of individuals. Wealth provides utility in a number of ways, for instance, by acting as a buffer against negative income shocks. Using the wealth component of the German Socio-Economic Panel (GSOEP), we find that, on average, members of western households exhibit a net worth more than twice as high as their eastern counterparts. This wealth gap remains roughly stable over time and is much more pronounced for upper parts of the distributions. In this paper, we analyze how much of this gap in per capita net wealth at different parts of the distribution can be attributed to observable factors such as permanent income or sociodemographic characteristics. We carry out our decomposition analysis via a reweighting approach. We find that for the lower part of the distribution, most of the gap can be attributed to the wealth determinants, while this share is much lower at the upper part. The most important contributing factors in this regard are the lower levels of income still prevailing in East Germany as well as differentials in labor market outcomes. Moreover, Germans in younger cohorts feature more similar levels of wealth and are more similar than the older generation. For them the success on the labor market is by far the most important factor. We also find that home ownership rates differ markedly between the two regions and play an important role for the wealth gap even though differences in housing prices also seem matter.
urn:nbn:de:bsz:21-dspace-656979
Keywords: D14; D31; D63; E21; 330; household finance; wealth distribution; wealth gap; decomposition methods; counterfactuals; distributional analysis